Perancangan Arsitektur Kontemporer pada Apartemen Millennial di Bsd City, Kabupaten Tangerang, Provinsi Banten - Miranti Eka Septia Haryanto; Putri Suryandari; Harfa Iskandaria (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2020)
The higher level of population density as a result of the development of big cities in Jabodetabek at a macro level has an impact on the need for housing. Moreover, BSD City then became a business concentration with limited residential land. This millennial apartment with a contemporary architectural concept can fulfill the need for vertical housing. As well as overcoming problems related to housing as a residence, as well as being able to provide comfort to millennial generation residents, most of whom are urban. The millennial generation prefers to live in residential areas that have an open space concept because they are more efficient, economical and multifunctional. Contemporary architectural design uses conventional materials and traditional materials that are dynamic and have no boundaries on the interior and exterior, such as wood, glass, exposed concrete and metal. Its appearance looks unique and seems anti-mainstream so it is very popular with millennial generations.